Edinburgh Days, or Doing What I Want to Do - Pickering, Sam, 1941- (Book collections on Project MUSE., 2007)
Part travelogue, part psychological self-study, Sam Pickering's Edinburgh Days, or Doing What I Want to Do is an open invitation to be led on a walking tour of Scotland's capital as well as through the labyrinth of the guide's swerving moods and memories. Along the way readers discern as much from Pickering's sensual observations of Scottish lives and landmarks as they do about what befalls the curious mind of an intellectual removed from the relations and responsibilities that otherwise delineate his days. Pickering spent the winter and spring of 2004 on a fellowship at the Institute for Advanced Studies in the Humanities at the University of Edinburgh, making his return to the city after a forty-year absence. Edinburgh Days maps the transition from his life in Connecticut, defined by family, academic appointments, and the recognition of neighbors and avid acolytes, to a temporary existence on foreign soil that is at once unsettlingly isolating and curiously liberating. Torn between labeling himself a tourist or a sojourner, Pickering opts to define himself as an "urban spelunker" and embarks on daily explorations of the city's museums, bookshops, pubs, antique stores, monuments, neighborhoods, and graveyards. His ambling tours include such recognizable sites as Edinburgh Castle, the Palace of Holyroodhouse, Castle Rock, the Museum of Childhood, the National Gallery, the Writers' Museum, the Museum of the People, the Huntly House, the John Knox House, the Royal Botanic Garden, and the Edinburgh Zoo. The holdings of city and university libraries present Pickering with the opportunity to revisit the works of a host of writers, both renowned and obscure, including Robert Louis Stevenson, Samuel Smiles, John Buchan, Tobias Wolfe, Russell Hoban, Patrick White, Hilaire Belloc, and Van Wyck Brooks. "I have long been a traveler in little things," he muses, and it is his fascination with minutiae that infuses this collection of essays with the dynamic descriptions, quirky observations, and jesting interludes that bring the historic city to life on the page and simultaneously recall the very best of Pickering's idiosyncratic style